BEND4: a novel prognostic biomarker in diffuse large B-cell lymphoma - Yanfang Wang; Zhenhao Zhang; Lianyong Xi; Hua Wang; Fei Dong (Discover Oncology)
Abstract Background BEN domain-containing protein 4 (BEND4) is implicated in various cancer-related processes, but its role in diffuse large B-cell lymphoma (DLBCL) remains unclear. This study examined BEND4’s impact on DLBCL prognosis through bioinformatics analysis. Methods BEND4 expression was analyzed across the cancer cell line encyclopedia (CCLE), human protein atlas (HPA), and the cancer genome atlas (TCGA) databases. Associations between BEND4 expression and survival outcomes, prognosis, and immune infiltration levels of DLBCL were evaluated via TCGA. Gene set enrichment analysis (GSEA) identified potential BEND4 biological functions. The predictive value of BEND4 and related genes for DLBCL mortality was assessed using time-dependent receiver operating characteristic curve (ROC) analysis. Findings were validated through qRT-PCR and cell proliferation assays. Results BEND4 was overexpressed at mRNA and protein levels in DLBCL. High BEND4 expression correlated with shorter survival, higher disease-specific mortality, and poor prognosis, emerging as an independent risk factor. GSEA revealed associations between BEND4 and chromatin remodeling, immune response, epigenetic regulation, and signal transduction. Immune infiltration analysis showed BEND4 expression was inversely correlated with eosinophils, cytotoxic cells, and Tgd cells infiltration. ROC analysis confirmed BEND4 and related genes as key predictors of DLBCL mortality at 1, 3, and 5 years. In vitro, BEND4 inhibition did not alter Riva cells proliferation but enhanced sensitivity of Riva cells to chemotherapy, including doxorubicin. Conclusion Elevated BEND4 levels were linked to poor prognosis and chemoresistance in DLBCL, potentially due to transcriptional regulation and immune suppression roles. BEND4 may represent a viable therapeutic target in DLBCL.